IKT 16 aka PSR J0058–7218: discovery of a 22 ms energetic rotation-powered pulsar in the Small Magellanic Cloud. Issue 1 (1st June 2021) - Maitra, C; Esposito, P; Tiengo, A; Ballet, J; Haberl, F; Dai, S; Filipović, M D; Pilia, M
ABSTRACT: We report here on the discovery with XMM–Newton of pulsations at 22 ms from the central compact source associated with IKT 16, a supernova remnant in the Small Magellanic Cloud (SMC). The measured spin period and spin period derivative correspond to 21.7661076(2) ms and 2.9(3) × 10 −14 s s −1, respectively. Assuming standard spin-down by magnetic dipole radiation, the spin-down power corresponds to 1.1 × 10 38  erg s −1 implying a Crab-like pulsar. This makes it the most energetic pulsar discovered in the SMC so far and a close analogue of PSR J0537–6910, a Crab-like pulsar in the Large Magellanic Cloud. The characteristic age of the pulsar is 12 kyr. Having for the first time a period measure for this source, we also searched for the signal in archival data collected in radio with the Parkes telescope and in γ-rays with the Fermi /LAT, but no evidence for pulsation was found in these energy bands.